ANALISIS KESIAPAN BELAJAR PADA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 1 SERASAN TIMUR - Jayatra, Rizky; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractLearning readiness is the initial condition that makes students ready to respond to a lesson given by the teacher in a certain way in any situation. The better students' learning readiness, the better the results they get in the learning activities they follow. Therefore researchers wanted to know more about the learning readiness of class VIII Serasan Timur Middle School 1. The general problem of this research was "How is learning readiness in class VIII students of Serasan Timur Middle School 1?".The method used was descriptive method with a quantitative approach that is a problem solving procedure by describing the distribution of learning readiness of class VIII students of Serasan Timur Middle School 1. While the data collection technique usedÂ  wasindirect communication techniques. The population as well as the sample in the study amounted to 52 students. The form of this study was a study survey. The data collection tool used was a questionnaire.Based on the results of data analysis showed that the learning readiness of class VIII students of Serasan Timur Junior High School 1 reached 79.88%, included in the good category.Â Keywords:Analysis Learning Readiness.